2015
DOI: 10.4238/2015.april.10.30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AFP gene silencing on Survivin mRNA expression inhibition in HepG2 cells

Abstract: ABSTRACT. We investigated the effects of alpha-fetoprotein (AFP) gene silencing on Survivin expression in HepG2 cells. Small interfering RNA technology was used to downregulate AFP expression in HepG2 cells. An enzyme-linked immunosorbent assay was used to measure AFP concentration in the supernatant before and after transfection. An MTT assay was used to detect cell proliferation activity before and after transfection. We performed flow cytometric analysis to detect the cell apoptosis rate, and reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moreover, high expression of BIRC5 or SKP2 protein also indicated poor prognosis in our TMA cohort. As previously mentioned, Fang et al suggested that silencing of AFP may reduce intracellular BIRC5 mRNA expression to promote apoptosis in HepG2 cells 67 . In lung adenocarcinoma, the high level of BIRC5 was related to advanced AJCC stage, T and N stages 68 .…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, high expression of BIRC5 or SKP2 protein also indicated poor prognosis in our TMA cohort. As previously mentioned, Fang et al suggested that silencing of AFP may reduce intracellular BIRC5 mRNA expression to promote apoptosis in HepG2 cells 67 . In lung adenocarcinoma, the high level of BIRC5 was related to advanced AJCC stage, T and N stages 68 .…”
Section: Discussionmentioning
confidence: 84%
“…Thus, siRNA targeting the AFP gene, designated as AFP -siRNA, has become one of the most promising strategies for inhibiting AFP expression. Reportedly, silencing of AFP can be achieved in the hepatoma cell line HepG2 by reducing BIRC5 (survivin) mRNA expression [ 13 ]. Also, the expression of AFP was completely inhibited in the overexpressed AFP hepatocellular carcinoma cell line (EGHC-9901) by the AFP -siRNA plasmid transfection system through apoptosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated expression of AFP in tumors and serum is found in 60%-80% of HCC patients (14) and correlates with poor prognosis (18). Although the function of AFP remains unclear, it has been reported to promote cell proliferation, suppress apoptosis, and act as an immunosuppressive agent (19)(20)(21)(22)(23), suggesting a potential role in disease progression.…”
Section: Introductionmentioning
confidence: 99%